Validity and reliability of the GymAware linear position transducer for squat jump and counter-movement jump height - Wadhi, T.; Rauch, J. T.; Tamulevicius, N.; Andersen, J. C.; De Souza, E. O. (Sports, 2018)
The purpose of this study was to assess the concurrent validity and test-retest reliability of a linear position transducer (LPT) for the squat jump (SJ) and counter-movement jump (CMJ) height. Twenty-eight subjects (25.18 ± 7.1 years) performed three SJs followed by three CMJs using a force plate concurrently with the LPT to test validity. Subjects returned on a separate day, at least 48 h apart, to measure test-retest reliability. A t-test showed a significant difference between the two devices for both SJ (p < 0.001) and CMJ (p < 0.001) while Bland-Altman analysis for validity revealed that the LPT overestimated jump height for both SJ (mean difference (MD) = 8.01 ± 2.93 cm) and CMJ (MD = 8.68 ± 2.99 cm). With regards to reliability of the LPT, mean intraclass correlation (ICC) for both SJ (ICC = 0.84) and CMJ (ICC = 0.95) were high, and Bland-Altman analysis showed mean differences lower than minimal detectable change (MDC) between the days for both SJ (MD = 1.89 ± 4.16 cm vs. MDC = 2.72 cm) and CMJ (MD = 0.47 ± 3.23 cm vs. MDC = 2.11 cm). Additionally, there was a low coefficient of variation (CV) between days for both SJ (CV = 3.25%) and CMJ (CV = 0.74%). Therefore, while the LPT overestimates jump height, it is a reliable tool for tracking changes in jump height to measure performance improvement and monitor fatigue.